The indigenous welfare economy and the CDEP scheme - Morphy, F. 1949-; Sanders, Will 1956- (ANU E Press, 2004)
The Community Development Employment Projects (CDEP) scheme represents a major adaptation of the Australian welfare system to the particular social and economic circumstances of indigenous people. Part I contains overview papers which place the CDEP program in its wider cultural, sociopolitical and economic contexts. The contributions in Part II address policy and policy-related issues which impact directly, or indirectly, on the structure and function of the CDEP scheme as a whole or of individual projects. Part III represents research based case-studies of particular CDEP projects and Part IV consists of short case studies from the perspective of the participants themselves
Keywords: Employment subsidies; Federal aid to community development; SOCIAL SCIENCE; Society and social sciences Society and social sciences; Sociology and anthropology; Sociology: work and labour; Sociology; Aboriginal Australians -- Employment -- Government policy; Employment subsidies -- Australia; Federal aid to community development -- Australia; aboriginal australians; australia; community development; employment; government policy; Community Development Employment Projects (Australia); Australia; Electronic books